2000
DOI: 10.1076/1380-3395(200002)22:1;1-8;ft132
|View full text |Cite
|
Sign up to set email alerts
|

Intervening with Everyday Memory Problems in Dementia of Alzheimer Type: An Errorless Learning Approach

Abstract: Dementia of Alzheimer Type (DAT) is increasingly detected at an earlier stage of the disorder, when interventions to assist with everyday memory difficulties might be most valuable. Some learning is possible in DAT and a number of factors have been identified which may facilitate performance, although applications to everyday memory problems have been limited. The concept of errorless learning has not previously been directly examined in relation to DAT, but might provide a useful additional strategy. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
214
1
23

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(246 citation statements)
references
References 48 publications
8
214
1
23
Order By: Relevance
“…However, Evans, Wilson, Schuri, Andrade, Baddeley, Bruna, Canavan, Della Sala, Green, Laaksonen, Lorenzi, & Taussik (2000) had mixed results: EL was successful for relearning names but not for route learning or putting information into an electronic aid. Studies by Clare, Wilson, Breen & Hodges (1999), Clare, Wilson, Carter, Gosses, Breen & Hodges (2000) Clare, Wilson, Carter, Hodges & Adams (2001), Clare, Wilson, Carter, Roth and Hodges (2002) and Clare, Wilson, Carter and Hodges (2003) have found that errorless learning can be useful for retraining facename associations, personal information and use of memory aids for people with dementia. These positive effects of errorless learning have been attributed to the interference of errors in learning when explicit memory is impaired Page et al, 2006).…”
mentioning
confidence: 99%
“…However, Evans, Wilson, Schuri, Andrade, Baddeley, Bruna, Canavan, Della Sala, Green, Laaksonen, Lorenzi, & Taussik (2000) had mixed results: EL was successful for relearning names but not for route learning or putting information into an electronic aid. Studies by Clare, Wilson, Breen & Hodges (1999), Clare, Wilson, Carter, Gosses, Breen & Hodges (2000) Clare, Wilson, Carter, Hodges & Adams (2001), Clare, Wilson, Carter, Roth and Hodges (2002) and Clare, Wilson, Carter and Hodges (2003) have found that errorless learning can be useful for retraining facename associations, personal information and use of memory aids for people with dementia. These positive effects of errorless learning have been attributed to the interference of errors in learning when explicit memory is impaired Page et al, 2006).…”
mentioning
confidence: 99%
“…Similarly, after providing a four-component program of case management, psychosocial rehabilitation, individual counseling, and training of staff for elderly in 13 licensed residential care facilities, Gottesman, Peskin, Kennedy, and Mossey (1991) found no change in cognition, instrumental activities, or psychiatric symptoms. However, recently Clare et al (2000) found that five participants with dementia (MMSE scores 21-26) who received individual interventions improved their everyday memory function, and maintained the gains at 6 months. Yet few nursing homes offer cognitive rehabilitation programs (Gabrel, 2000;Kane, Chen, Blewett, & Sangl, 1996;Lopez & Mermelstein, 1995;Moseley, 1995;Wilson, 1993).…”
mentioning
confidence: 99%
“…Esta oscilação deverá ser compreendida, na opinião dos autores, em parte pela falta de adequação da introdução de determinada ajuda externa, no quotidiano de um indivíduo, isto é, o envelhecimento não é homogêneo entre os indivíduos, devendo ser avaliado cada sujeito no sentido de se percepcionar qual a melhor estratégia de compensação a introduzir. Neste sentido, o estudo de Clare et al (2000), vem acentuar a importância de individualizar e ajustar a intervenção, pois o paciente F, que apenas usou ajuda externa electrónica, nunca se habituou complemente à mesma, tendo-a abandonado, logo após a fase de intervenção. É portanto da opinião dos autores que o uso de ajudas externas deve integrar-se na avaliação de necessidades e no planeamento diário das actividades, traduzindo-se numa intervenção com eficá-cia e com continuidade no follow-up.…”
Section: Fonteunclassified
“…Segundo Bourgeois (1992), Hanley (1986), Kurlychek (1983), citados por Clare et al, 2000), o treino das ajudas externas à memória em pessoas idosas com demência, tem sido investigado num pequeno número de estudos, no entanto Bourgeois et al (2003), afirma que desde os anos 90 o número de estudos publicados, documentando a eficácia das intervenções em indivíduos com demên-cia, têm aumentado bastante, tendo sido testados mais ao nível das lesões cerebrais e da demência, e os resultados demonstram eficácia no follow-up, como refere o estudo de Wilson et al (1997).…”
Section: Fonteunclassified